People with autism behaving badly : helping people with ASD move on from behavioral and emotional challenges - Clements, John, 1946 December 1- (Jessica Kingsley Publishers, 2005)
People with autism spectrum conditions may often behave in ways that cause difficulties for themselves and those who care for them. People with Autism Behaving Badly offers effective, long-term strategies to help resolve common problem behaviors such as physical aggression, self-injury, verbal abuse, rudeness and property damage. The book is organized around the common messages conveyed by behaviors and some of the underlying issues that drive these messages. Practical ideas for intervention are provided and illustrated by case examples. A range of exercises help to build understanding of the.